Territorialization: Situational diagnosis for planning health actions in a coverage area of the family health strategy - Oliveira , Ana Caroline Milhomens de; Andrade , Déborah Alves; Araújo , Geovanna Martins; Brandão , Isabella Iasmim Mascarenhas; Paiva , Juliana Vidal Batista; Rodrigues , Karen Bianca Alves Pereira; Padovani , Laura Stefani Guimarães; Reis , Samara Pereira; Andrade , Ana Paula Bandeira Matos de Serpa (Seven Editora, 2024)
Introduction: Health is a universal right and a responsibility of the State, especially in the organization of health services where the basic units are located. Territorialization, together with situational diagnosis, is described as an essential process to identify health priorities and direct effective actions to meet the unique demand of each community. Objective: To describe the importance of territorialization and situational diagnosis for the planning of health actions aimed at the individual and collective priorities of the community of an area enrolled in a health unit in the municipality of Porto Nacional. Methodology: Qualitative and descriptive approach, with emphasis on bibliographic research and situational diagnosis of micro-area 61 of the territory of the Mãe Eugênia Basic Health Unit, Porto Nacional - Tocantins. Result and Discussion: Based on the study carried out in the area covered by the 201 families living in the neighborhoods that make up the area in question, it was possible to identify the risks and classify these families according to their living conditions. This research provided a differentiated and attentive look of the researchers, who experienced in practice an activity developed by the Community Health Agents, who are fundamental in this process. Final considerations: Territorialization is responsible for bringing the collection of quantitative and qualitative information, population number and situational diagnosis that will provide the planning of actions, emphasizing the interaction between the community and health professionals, in addition to the crucial role of Community Health Agents in this process, for the promotion of care for the population. DOI:https://doi.org/10.56238/sevened2024.010-041